PENGARUH DINESERV QUALITY TERHADAP KEPUASAN PELANGGAN BIMA N ZAIN CAFE DI KABUPATEN BANGKALAN - Vania Novianti Sahid; Muh. Syarif (Management Department of Economics and Business Of Trunojoyo Madura University, 2022)
The purpose of this study was to determine the effect of Tangible, Reliability, Responsiveness, Assurance, and Emphaty on Customer satisfaction at Bima n Zain Cafe in Bangkalan Regency. By measuring service quality using Dineserv indikators based on 5 dimensions of service quality. This research was conducted with quantitative methods, the sampling technique used is nonprobability sampling with purposive sampling method as sample determination. The sample of this research was 100 respondents, and the population in this research are Bima n Zain Cafe’s customers who have visited and made some purchase at Bima n Zain Cafe.The results of this study indicate that the Tangible variable has no positive and insignificant effect on customer satisfaction, the Reliability and Responsiveness variables have a positive and significant effect on customer satisfaction. While Assurance and Emphaty have a positive but not significant effect on customers satisfaction. However, simultaneously, it has a positive and significant effect on customer satisfaction of Bima n Zain in Bangkalan Regency.